Local Wisdom and Village Governance in Disaster Mitigation: Evidence from Tulungrejo Village - Sihidi, Iradhad Taqwa; Romadhan, Ach. Apriyanto; Dharmala, Bayu; Ermylina, Eva (Universitas Muhammadiyah Malang, 2026)
Frequent floods and landslides in Tulungrejo Village, Batu City, require locally grounded mitigation strategies that are adaptive to the village’s ecological and social conditions. This study aims to analyze the role of local wisdom in the disaster mitigation system in Tulungrejo Village, Batu City, by emphasizing the integration of traditional knowledge, social systems, and village institutional support. The research method used is qualitative-descriptive through field observations, in-depth interviews, and documentation studies. The results show that local wisdom-based mitigation practices are operationalized through terracing techniques, small retention basins, and adaptive land management, which function as preventive mechanisms embedded in daily agricultural activities. In addition to ecological practices, the community’s social system serves as an effective medium for risk communication, enabling rapid information exchange and collective response through informal networks and village deliberation forums. Village government support, particularly through pre-disaster budget allocation, facilitation of community forums, and integration of local knowledge into planning processes, strengthens the institutionalization of mitigation practices. The interaction between ecological knowledge, social communication, and institutional support forms a collaborative and adaptive mitigation system. However, challenges remain in the regeneration and documentation of local knowledge, which may affect the long-term sustainability of community-based mitigation.